Pengaruh Model Pembelajaran STAD Berbantuan Media Monopoli Ragam Budaya Terhadap Hasil Belajar IPS Siswa Kelas 4 SD N Gunungsari - Purnasiwi, Anggraeni Ratna (Prosiding University Research Colloquium, 2021)
This study aims to examine the effect of the STAD learning model assisted by multicultural monopoly media on social studies learning outcomes for 4th grade students of Gunungsari State Elementary School. This study uses an experimental method with the research design used is a pre-experimental one group pre-test - post-test design. The research subjects were 4th grade students of SD Negeri Gunungsari. The sample in this study amounted to 15 students. Data collection techniques used are multiple choice tests and documentation.The results showed that the hypothesis test using the Wilcoxon test showed that the Asymp value. Sig is <0.001. So, because sig < 0.005, Ho is rejected while Ha is accepted, which means that there is an influence of the STAD learning model assisted by the monopoly of cultural diversity on the social studies learning outcomes of 4th grade students of Gunungsari State Elementary School. It is shown by the existence of students’ interest in learning media and the attitude of cooperation between groups that affect students’ social studies learning outcomes which increase. This is an evaluation for educators that applying learning models and media can affect student learning outcomes.